2018
DOI: 10.1192/bjp.2017.51
|View full text |Cite
|
Sign up to set email alerts
|

Community treatment orders: an analysis of the first five years of use in England

Abstract: The number of new CTOs each year ranged between 3834 and 4647. The number subject to a CTO per 100 000 population increased from 6.4 in 2009/10 to 10.0 in 2013/14. There was variation between NHS trusts in the use of CTOs when compared with the number of involuntary detentions CONCLUSIONS: The number of patients on CTOs increased year on year. Those on forensic sections were more likely to be discharged on a CTO than those on civil sections. There was considerable variation in the pattern of use between hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
0
15
1
Order By: Relevance
“…30 In England, routine statistics suggest significant differences between service providers, 25 a point emphasised by recent research exploring these data. 29,31 Again, however, little attempt has been made to relate spatial variations in CTO use to patient demographic or clinical characteristics, or, indeed, to the characteristics of the areas or service providers themselves.…”
Section: Patterns Of Usementioning
confidence: 99%
“…30 In England, routine statistics suggest significant differences between service providers, 25 a point emphasised by recent research exploring these data. 29,31 Again, however, little attempt has been made to relate spatial variations in CTO use to patient demographic or clinical characteristics, or, indeed, to the characteristics of the areas or service providers themselves.…”
Section: Patterns Of Usementioning
confidence: 99%
“…Trevithick and colleagues noted that trusts serving large urban centres have higher rates of CTO use. 8 Studies have also shown that there are higher rates of CTO use in trusts that provide specialist services for people with intellectual disability. 8,31 Another reason for differences in levels of use of CTOs in different parts of the country could be continuing uncertainty about the clinical effectiveness of this approach to helping people with psychosis.…”
Section: Implications Of Study Findingsmentioning
confidence: 99%
“…8 Studies have also shown that there are higher rates of CTO use in trusts that provide specialist services for people with intellectual disability. 8,31 Another reason for differences in levels of use of CTOs in different parts of the country could be continuing uncertainty about the clinical effectiveness of this approach to helping people with psychosis. While the results of the OCTET trial and other randomised trials of compulsory community treatment suggest that CTOs do not reduce use of in-patient services or lead to improved mental health or quality of life, 17,18 questions have been raised about whether the results of these trials can be generalised to routine clinical settings 37 and many psychiatrists remain convinced of their benefit.…”
Section: Implications Of Study Findingsmentioning
confidence: 99%
See 2 more Smart Citations